Alain Badiou – Philosophical Tango with the Elusive Theatre - Denkova, Lidia (Sledva : NBU Journal of Humanities and Arts, 2019)
Philosophical commentary on Alain Badiou’s dialogic theatre pamphlet and his broader personal engagement with theatre and cinema.